A new species of the subgenus Idopterum Hampson, 1894 of the genus Ammatho Walker, 1855 from China (Lepidoptera: Erebidae: Arctiinae: Lithosiini), with redefinition of the subgenus Idopterum - Huang, Si-Yao; Volynkin, Anton V.; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2020)
A new species of the subgenus Idopterum Hampson, 1894 of the genus Ammatho Walker, 1855, Ammatho (Idopterum) wuchunshengi Huang, Volynkin & Wang sp. nov. is described from southeastern Yunnan, Southwestern China. The autapomorphies of Idopterum are redefined and the features in juxta and aedeagus vesica are corrected and added, respectively. Adults and genitalia of the new species and related species are illustrated.